Pragmatic Functions in Ahmed El-Metouakel’s Project: An Applied Study of Selected Models from Epistemic Absurd Narrative through “Marasī al-Sirr al-Mughtarib” by Salahh Ghilous - kellal, zohra; ammari, azzeddine (El Omda in Linguistics and Discourse Analysis, 2023)
This research seeks to delve into functional deliberative studies, by shedding light on Ahmed Al-Mutawakel’s research in his study of the pragmatic functions related to the Arabic language, within his linguistic project, seeking to invest what Western functional studies have excelled in, taking into account the specificity of the Arabic language. It is his responsibility to try to identify these functions with their components mentioned by Al-Mutawakkil, and to strive to make the model of the absurdist customary shearing "The Anchors of the Expatriated Secret" an applied field for Ahmed Al-Mutawakel's approach. Keywords: deliberative functions, Arabic language, project, For this approach.